Hypokalaemia with flaccid paralysis following high-voltage electrical injury in an adolescent patient. (October 2019) - Bird, R; Naji, S; Vowles, B; Shaw, A; Martin, NA
The authors present a case report of a previously healthy 15-year-old male who experienced global weakness in the presence of profound hypokalaemia following a high-voltage electrical arc injury. The clinical picture is discussed in the context of our evolving understanding of electrical injuries and potassium homeostasis.